Mesenchymal PLAG1 Tumor With PCMTD1-PLAG1 Fusion in an Infant: A New Type of "Plagoma". (20th January 2022) - Tomás-Velázquez, Alejandra; Surrey, Lea F.; Miele, Evelina; Li, Marilyn M.; Alaggio, Rita; Goitz, Robert J.; Reyes-Múgica, Miguel; Salgado, Cláudia Maria
Abstract: In the past decade, there have been major advances in knowledge related to mesenchymal tumors, and new genetic alterations are being delineated. We report a mesenchymal spindle cell neoplasm harboring a novel gene fusion in an infant. Histopathologically, the neoplasm shared some features with sclerosing perineurioma, but immunohistochemically, EMA was negative, whereas GLUT1, NK1-C3, and BCOR were positive. Next-generation sequencing revealed a PCMTD1–pleomorphic adenoma gene 1 (PLAG1 ) fusion. PLAG1 contributes to the expression of a variety of genes implicated in regulating cell proliferation, and PCMTD1 has been related to the development of certain carcinomas. Recently, other soft tissue tumors in young children associated with PLAG1 fusion variants have been reported. Perhaps, mesenchymal neoplasms presenting PLAG1 fusions with different genes would confirm a specific group (PLAG mesenchymal tumours or "plagomas") in the near future.